Implementation of Policy Procedures for Filling High Leader Positions through Open Selection in the South Bolaang Mongondow Government Environment: Implementation of Policy Procedures for Filling High Leader Positions through Open Selection in the South Bolaang Mongondow Government Environment - AWALUDIN LAMALANI; Titin Dunggio; Imam Mashudi (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This study aims to find out how the implementation of policies and what factors determine the implementation of policies on procedures for filling high-ranking pratama positions in South Bolaang Mongondow Regency. The method used is a qualitative method with a descriptive approach. Informants in this study were the Regent, Regional Secretary, Secretary of BKPSDM, Head of Division and Sub-Section of BKPSDM. Data analysis through data reduction, data display and conclusion drawing/verification. The results of the study showed that at the preparation stage, there were no Independent Assessors. At the implementation stage, there is a lack of ASN human resources participating in the auction of positions. At the stage of monitoring and evaluation not running effectively, there are several High Leadership Officials who have held positions for 5 (five) years, and have not been reassessed related to the suitability of competencies and positions occupied. Factors that affect implementation: Communication, an inhibiting factor because of the existence of the Pansel Team and Assessor Team; Resources, become an inhibiting factor because the ASN candidates for bidding positions that meet the requirements are still very lacking; Disposition is a supporting factor because the understanding and response of program implementers is good; bureaucratic structure,